2018
DOI: 10.1016/j.jasrep.2018.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Mollusk carbonate thermal behaviour and its implications in understanding prehistoric fire events in shell middens

Abstract: Archaeological shell middens are particularly important for reconstructing prehistoric human subsistence strategies. However, very little is known about shellfish processing, especially when related to the use of fire for dietary and disposal purposes. To shed light on prehistoric food processing techniques, an experimental study was undertaken on modern gastropod shells (Phorcus lineatus). The shells were exposed to high temperatures (200-700 °C) to investigate subsequent mineralogy and macroand microstructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 99 publications
1
25
0
Order By: Relevance
“…This reaction rate is considerably accelerated and occurs at lower temperatures if a powdered aragonite is used in the alteration experiment (Guo et al., 2019). Dry heating (or “roasting”) experiments revealed that the transition to calcite requires more time and/or higher temperatures, but is nevertheless accompanied by an oxygen isotopic shift in the carbonate (Milano et al., 2018; Müller, Staudigel, et al., 2017; Staudigel & Swart, 2016). This isotopic shift, which occurs in absence of interaction with an outside medium, is believed to be caused by a set of exchange reactions that occur with internal fluids (Moon et al., 2020; Pederson, Mavromatis, et al., 2019; Pederson, Weiss, et al., 2019; Uemura et al., 2019), and/or internal organic material (Li et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This reaction rate is considerably accelerated and occurs at lower temperatures if a powdered aragonite is used in the alteration experiment (Guo et al., 2019). Dry heating (or “roasting”) experiments revealed that the transition to calcite requires more time and/or higher temperatures, but is nevertheless accompanied by an oxygen isotopic shift in the carbonate (Milano et al., 2018; Müller, Staudigel, et al., 2017; Staudigel & Swart, 2016). This isotopic shift, which occurs in absence of interaction with an outside medium, is believed to be caused by a set of exchange reactions that occur with internal fluids (Moon et al., 2020; Pederson, Mavromatis, et al., 2019; Pederson, Weiss, et al., 2019; Uemura et al., 2019), and/or internal organic material (Li et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This observed ~200 yr offset may be explained by diagenetic alteration of the outer layer. High temperatures derived from cooking or burning activities (>300°C) may cause significant changes in the geochemistry of the shell (Milano et al, 2016, 2018). However, the shells analyzed here did not show visual evidence of heat exposure, and further research is needed to evaluate the potential effects of diagenetic alteration in radiocarbon results.…”
Section: Discussionmentioning
confidence: 99%
“…One study, which included several shell species from the Gulf of Oman, demonstrated that burned shells not only provided reliable 14 C ages, but also elucidated some patterns of shell processing in the past (Lindauer et al 2018). Microstructure patterns of the different shell layers helped to identify processes and mineral transitions from aragonite to calcite of a semi-burnt shell (Lindauer et al 2018;Milano et al 2018).…”
Section: Contamination Isotopic Exchange and Recrystallizationmentioning
confidence: 99%